Dampak Kontribusi Pengembangan Pariwisata Terhadap Ekosistem Pesisir di Kabupaten Nias Selatan - Benny Alfred Sarumaha; Erika Revida; Lita Sri Handayani (Jurnal Serambi Engineering, 2023)
The reason for this study was to decide the commitment of the travel industry to the waterfront biological system of South Nias Rule through the travel industry advancement. The travel industry improvement in South Nias not entirely set in stone by attractions, openness, administrations and supporting exercises. then, at that point, estimated how much the commitment of these exercises to the advancement of the travel industry in South Nias Regime. Polls, meetings and documentation were utilized as information assortment methods. This study utilizes a quantitative strategy utilizing optional information got from the Focal Department of Measurements (BPS) and related organizations. The number of respondent in this exploration is individuals who are in vacationer areas. The example populace of this study is essential for the local area in the vacationer location region under study. The strategy for investigation of this examination utilizes basic direct relapse investigation, commitment investigation and elucidating investigation. In light of the aftereffects of information examination, it tends to be reasoned that the portion of the travel industry improvement in the portion of the travel industry income is tiny, in particular a normal of 0.68% in 2018-2020, so it very well may be presumed that it doesn't make adverse consequence the environment.